Dosimetric Outcome of Half Beam Block and Junction Translation (Feathering) Technique in Hot Spot Management of PALNs Involved Patient of Ca Cervix using 3DCRT and Hybrid IMRT Technique: A Case Study - Muhammad Bilal Durrani (Diponegoro University Semarang Indonesia, 2026)
Positive Para Aortic Lymph Nodes (PALNs) involved patient of Ca-cervix/Endometrium requires large treatment fields to cover entire planning target volume (PTV) for radiation therapy (RT). RT treatment plan were generated to the contoured PTVusing 3DCRT-3DCRT and IMRT-3DCRT (Hybrid IMRT) for single iso-centric and dual iso-centric technique. Single iso-centric technique was used for PTV pelvis and PTV aorta for field size (F.S) max < PTV and dual iso-centric was used when (F.S) max > PTV.For single isocentric setup the hot spot at the junction of 3DCRTpelvis -3DCRTaorta was managed by half beam block and optimized using field in field technique (FIF) while in case of 3DCRTaorta-IMRTpelvis the hotspot was managed by changing the position of independent Y-Jaw in IMRTpelvis treatment planonly. For condition of (F.S) max< PTV with dual isocentric set up the hot spot at the junction of PTVPelvis andPTVaorta was reduced to acceptable limits by translating the Y-jaw position in IMRT pelvisonly, whereas due to smaller junction gap of 1.5 cm between 3DCRTpelvis-3DCRTaorta treatment plan the hot spot was managed by only applying FnF technique in 3DCRTpelvis treatment plan.